Social and Cultural Impact during an Emerging Infectious Covid-19 Outbreak: A Review Study - Andi Sri Hastuti Handayani; Rian Adi Pamungkas; Andi Mayasari Usman (International Journal of Nursing and Health Services (IJNHS), 2021)
A novel coronavirus (Covid-19) was a global pandemic worldwide. This review aimed to explore and describe the Covid-19 outbreak's impact on socio and culture during a pandemic situation. Electronic databases from different sources were included to extract the relevant articles. Initially, terms to retrieve related studies were “social impact," “cultural impact," Covid-19”. The results showed that five key issues on socio and cultural during pandemic situation including 1) social vulnerability and community resilience; 2) stigma, prejudice, and discrimination; 3) social avoidance, rejection, and denials of healthcare providers; 4) family dynamics: domestic violence; and 5) severe projection of the poverty rate. The expected benefit of this study to explain the valuable information regarding socio and cultural impact